2017
DOI: 10.1021/acs.inorgchem.7b00952
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Coordinate Dysprosium Single-Ion Magnet with Trigonal-Prismatic Geometry

Abstract: A mononuclar six-coordinate dysprosium complex was synthesized and structurally and magnetically characterized. X-ray structural analyses show trigonal-prismatic coordination geometry of the Dy center. Slow relaxation of magnetization in the absence of a direct-current field and magnetic hysteresis up to 3.0 K could be observed, indicating its single-ion-magnet behavior. Arrhenius fitting and ab initio calculations suggest that the magnetic relaxation process may not occur through the Orbach process at high te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Complex 6.4 was reported by Liu et al. in 2017, [68] and has the Dy III centre in a trigonal prismatic geometry (Figure 11). It showed magnetic hysteresis up to 3 K in the absence of an external magnetic field, with a U eff of 190 K. Giansiracusa et al reported 6.5 recently [69] .…”
Section: Mononuclear Dy Alkoxide and Aryloxide Smmsmentioning
confidence: 76%
“…Complex 6.4 was reported by Liu et al. in 2017, [68] and has the Dy III centre in a trigonal prismatic geometry (Figure 11). It showed magnetic hysteresis up to 3 K in the absence of an external magnetic field, with a U eff of 190 K. Giansiracusa et al reported 6.5 recently [69] .…”
Section: Mononuclear Dy Alkoxide and Aryloxide Smmsmentioning
confidence: 76%
“…[27][28] However, the presented systems exhibit a crystalloprahically imposed trigonal symmetry which should provide mixed m J states. Although, zero-field slow relaxation in six-coordinate lanthanide complexes is rather scarce, [45][46][47] complex 2 is the first example of a zero-field undiluted SMM with such imposed symmetry. This suggests that despite being weak, the exchange interactions may affect the relaxation.…”
Section: Scheme 1 Synthesis Of Complexes 15mentioning
confidence: 99%
“…]} and HN* = HN(SiMe3)2) with trigonal-prismatic coordination geometry, exhibited a high energy barrier Ueff = 190 K under a zero dc field [33]. It is crucial to note that the magnetic axis is approximately collinear to the direction of [N*] − -N, resulted from the strong axial-ligand field improved by the short Dy-N([N*] − ) bond lengths of 2.296 Å.…”
Section: Introductionmentioning
confidence: 99%